High-resolution MRI with cardiac and respiratory gating allows for accurate in vivo atherosclerotic plaque visualization in the murine aortic arch. - Wiesmann, F; Szimtenings, M; Frydrychowicz, A; Illinger, R; Hunecke, A; Rommel, E; Neubauer, S; Haase, A (2003)
Genetically engineered mouse models provide enormous potential for investigation of the underlying mechanisms of atherosclerotic disease, but noninvasive imaging methods for analysis of atherosclerosis in mice are currently limited. This study aimed to demonstrate the feasibility of MRI to noninvasively visualize atherosclerotic plaques in the thoracic aorta in mice deficient in apolipoprotein-E, who develop atherosclerotic lesions similar to those observed in humans. To freeze motion, MR data acquisition was both ECG- and respiratory-gated. T(1)-weighted MR images were acquired with TR/TE approximately 1000/10 ms. Spatial image resolution was 49 x 98 x 300 micro m(3). MRI revealed a detailed view of the lumen and the vessel wall of the entire thoracic aorta. Comparison of MRI with corresponding cross-sectional histopathology showed excellent agreement of aortic vessel wall area (r = 0.97). Hence, noninvasive MRI should allow new insights into the mechanisms involved in progression and regression of atherosclerotic disease.